2017
DOI: 10.1007/s11104-017-3365-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-species intercropping of barley cultivars and legume species, as affected by soil phosphorus availability

Abstract: Aims Intercropping can improve plant yields and soil phosphorus (P) use efficiency. This study compares inter-and intra-species intercropping, and determines whether P uptake and shoot biomass accumulation in intercrops are affected by soil P availability. Methods Four barley cultivars (Hordeum vulgare L.) and three legume species (Trifolium subterreneum, Ornithopus sativus and Medicago truncatula) were selected on the basis of their contrasting root exudation and morphological responses to P deficiency. Monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 45 publications
4
38
0
Order By: Relevance
“…In accompanying greenhouse studies, these authors were able to identify rhizosphere acidification (reduction from pH 5.5 to 3.5) by faba bean and root intermingling between maize and faba bean as the underlying mechanisms allowing for greater P uptake by intercropped maize. Similarly, Darch et al (2018) reported 10 to 70% greater P accumulation in pot-grown intercrops of barley (Hordeum vulgare L.) and green manure legumes relative to the crops grown alone, with greater benefits at lower levels of P fertilization; this was attributed to complementary P use among the intercropped species. In contrast, in a pot study investigating a wheat-faba bean intercrop in a low-P soil, Li et al (2016) found that while P deficiency stimulated root exudation by faba bean, the amount of P mobilization by faba bean was not sufficient to increase P supply to the intercropped wheat.…”
Section: Cropping System Design and Phosphorus Use Efficiencymentioning
confidence: 94%
See 3 more Smart Citations
“…In accompanying greenhouse studies, these authors were able to identify rhizosphere acidification (reduction from pH 5.5 to 3.5) by faba bean and root intermingling between maize and faba bean as the underlying mechanisms allowing for greater P uptake by intercropped maize. Similarly, Darch et al (2018) reported 10 to 70% greater P accumulation in pot-grown intercrops of barley (Hordeum vulgare L.) and green manure legumes relative to the crops grown alone, with greater benefits at lower levels of P fertilization; this was attributed to complementary P use among the intercropped species. In contrast, in a pot study investigating a wheat-faba bean intercrop in a low-P soil, Li et al (2016) found that while P deficiency stimulated root exudation by faba bean, the amount of P mobilization by faba bean was not sufficient to increase P supply to the intercropped wheat.…”
Section: Cropping System Design and Phosphorus Use Efficiencymentioning
confidence: 94%
“…The P benefits associated with intercrops tend to be more pronounced when soil‐available Pi is relatively low; however, under extremely low Pi availability, overall productivity of intercrops remains poor (Tang et al, 2016; Darch et al, 2018). Intercropping also risks interspecies competition for P (Simpson et al, 2011).…”
Section: Cropping System Design and Phosphorus Use Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The accepted manuscripts cover an appropriate range of topics related to organic phosphorus. This issue contains papers that we can class as 'reviews' (two papers, George et al 2017 andMenezesBlackburn et al 2017), 'plant centric' (Li et al 2017 andDarch et al 2017), 'soil centric' (three papers, Stahr et al 2017;Missong et al 2017 andSpain et al 2018) 'microbial centric' (two papers Nassal et al 2017 andGaiero et al 2017), 'analytical' (two papers, Adams et al 2017 andWhitfield et al 2017) and 'systems' (two papers Neal et al 2017). An additional historical overview paper has also been published from the Workshop (Haygarth et al 2018).…”
mentioning
confidence: 99%